Metode Pengembangan Potensi Wirausaha Ekonomi Produktif Di Kabupaten Bima Dan Kota Bima Untuk Mendukung Tahun Pariwisata Provinsi Ntb 2021 - Dedy Febry Rachman; Sri Anita Rachman; Muhammad Innuddin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The purpose of this study is to encourage an increase in business activity and creativity in community groups in Bima Regency and Bima City, Obtain information related to the economic potential of the region, Obtain information related to various obstacles faced by the community, especially related to the development of productive economic enterprises, Explore information related to local government policies in Bima Regency and Bima City, especially those related to the development of productive economic enterprises. The methodology of this research is a research and development (RD) approach covering ten stages starting from (1) research and information collecting; (2) planning; (3) develop preliminary form of product; (4) preliminary field testing; (5) main product revision; (6) mainfield testing; (7) operational product revision; (8) operational field testing; (9) final product revision; (10) dissemination and implementation. The results of the study show that the Agriculture, Forestry, and Fisheries Sector is still the largest contributor to the economy of Bima Regency. According to BPS data, in 2019 this sector contributed 43.50 percent to the economic posture of Bima Regency and the Bima City Economy was mostly contributed from the trade sector where, in 2019 this sector contributed 25.11 percent to the economic structure of Bima City